Editorial Board - bikotetik, admin (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
The Editorial Board page provides information about the team of editors who play a crucial role in maintaining the quality and academic integrity of this journal. The board comprises scholars and professionals with strong expertise in their respective fields and extensive experience in scholarly review and publication. Through a spirit of collaboration, the editorial team is responsible for the selection, evaluation, and editing of submitted manuscripts to ensure that each publication meets high academic and ethical standards. The presence of the Editorial Board reflects the journal's commitment to delivering credible, relevant, and impactful scientific contributions to the advancement of knowledge and society.